Biochemical lesions and lethal synthesis - Peters, Rudolph Albert, Sir (International series of monographs on pure and applied biology. Division, Modern trends in physiological sciences., 1963)
International Series of Monographs on Pure and Applied Biology, Volume 18: Biochemical Lesions and Lethal Synthesis focuses on biochemical lesions. The book first discusses biochemical lesions in thiamine deficiency and arsenical substances and biochemical lesions. The text also examines biochemical lesions in mustard gas poisoning. Concerns include sulfone, sulfoxide, vesication, and cross-linking. The book also describes inhibitors of enzymes containing thiol groups and toxicity. Cell division, thiol agents, epidemic dropsy, and sanguinarine are highlighted. The text further focuses on letha.